A Descriptive study of television shopping viewers on Metro Manila - Uy, Vivien Ang 1979-; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This study was conducted to determine the characteristics of television shopping viewers. The survey method was used for it is the most appropriate research method for conducting an in-depth analysis of the different characteristics of television shopping viewers. The researcher conducted a survey among two hundred respondents in four cities in Metro Manila, namely, Quezon City, Manila, Pasig, and Marikina City. The survey was divided into four parts: demographic characteristics of the respondents, level of exposure to television shopping, preferences, and effectiveness of television shopping. The results showed that the viewers of television shopping programs were a select kind of audience. The profile of a typical viewer would be mostly a single female, below 30 years old, and either a student or professional. Her monthly family income may vary. In terms of viewing habits, the viewer would watch once to twice a week for a period of thirty minute per sitting, usually during evening. He preferred to watch television shopping programs through cable channels. The reasons why the viewer watched were for information on various products and for entertainment. He or she watched advertisements repeatedly, from start to end, while doing other things. When it came to viewer preferences, they preferred programs selling kitchenware items, exercise and fitness equipment, and health and beauty products. The reasons why they preferred such programs were that the programs had the most information on a product, at the same time, the programs had the greatest array of new products. Half of the viewers could possible become buyers. For those who did not, this was for reasons of lack of money and expensive products. Kitchenware remained the preferred item to buy, followed by health and beauty products. Most of the buyers forgot the brand names of the products they bought. The buyers bought products only once to fulfill a need. Most of them decided with their families first before buying and the main reasons why they bought through television shopping were because of availability of products and the convenience of television shopping. Most of the buyers were satisfied with their buy due to the good value and effectiveness of the product. They believed they will buy again through television shopping. Almost all of the respondents enjoyed the service provided by television shopping. They believed it is an alternative medium for shopping and would most likely use it in the future.
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Teleshopping -- Philippines